Assessment of Seawater Intrusion and Associated Environmental Impacts on the Al-Qarabulli Coastal Aquifer, Libya (Comprehensive Journal of Science, 2025)
Seawater intrusion into groundwater aquifers is a natural phenomenon that commonly occurs in coastal regions due to the encroachment of seawater into freshwater reservoirs. This process leads to the degradation of groundwater quality, directly impacting the availability of potable water—particularly in populated areas that rely fully or partially on groundwater as a primary water source.As part of a scientific investigation conducted in the Al-Qarabulli region, water samples were collected from 12 wells located at varying distances from the coastline, ranging from 200 meters to 10 kilometers. The analysis involved measuring the concentrations of sodium, potassium, chloride, and magnesium ions. Additionally, the extent of seawater intrusion was assessed using the Jones Index and Base Exchange Index (BEX)
Keywords: Al-Qarabulli, Coastal aquifers, Groundwater quality, Hydrochemical indices, Seawater intrusion.